Diagnostics and prediction of intracranial hypertension on primary computed tomography in patients with severe traumatic brain injury - A. V. Oshorov; K. R. Muradyan; A. M. Turkin; D. M. Chelushkin; Ya. A. Latyshev; E. V. Aleхandrova; Yu. V. Strunina; G. V. Danilov; I. A. Savin; A. D. Kravchuk (Вестник анестезиологии и реаниматологии, 2023)
The objective was to compare the optic nerve sheath diameter measured by CT (ODSN-CT) with the level of compression of the mesencephalic  cisterns and the midline shift in the diagnosis and prediction of intracranial hypertension (ICH) during the first 3 days after brain injury. Materials and methods. We examined 90 patients with TBI, the average age was 34.2 ± 13 years, GCS < 9. All patients had invasive ICP monitoring.  At the time of implantation of the ICP sensor, intracranial hypertension (ICH) was in 11 (12%) patients; later, during the first 3 days, the development of ICH was in 58 (64%) patients. All patients underwent computed tomography of the head at the time of hospitalization: mesencephalic  cisternae was compressed in 57 (63%) and midline shift was observed in 34 (38%) patients, mean value of ONSD-CT was 7.26 ± 0.9 mm, maximum  value of ONSD-CT was 7.34 ± 0.9. We used correlation analysis, logistic regression and ROC-analysis.Results. The level of mesencephalic cisternae compression, mean and maximum value of ONSD-CT correlated with the ICP value measured at the  time of ICP sensor implantation and during the first 72 hours after brain injury (p < 0.05). Midline shift did not correlate with ICP value measured  at the time of sensor implantation and during the first 72 hours after brain injury (p > 0.05). In the diagnosis of ICP > 20 mm Hg at the time of  implantation of the sensor – the average ONSD-CT, AUC 0.902 ± 0.046 (0.812; 0.991), cut-off 7.8 mm with sensitivity and specificity of 82 and  80%, respectively. When predicting ICP > 20 mm Hg in the first 72 hours - the maximum ONSD-CT, AUC 0.815 ± 0.047 (0.724; 0.907), cut-off  7.1 mm with sensitivity and specificity of 85 and 66%, respectively.Conclusions. The ONSD-CT parameter is an independent diagnostic and prognostic criterion of ICH in the first 3 days in patients with severe  TBI. The mean ONSD-CT can be used to diagnose ICH along with such signs of ICP as level of mesencephalic cisterna compression and midline  shift and to make a decision on invasive ICP monitoring. The maximum value of ONSD-CT can be used to assess the probability of ICH in the  first three days after TBI